Effect of Phase Transitions Between a-Tricalcium Phosphate and b-Tricalcium Phosphate on the Setting Properties of Novel Strontium-Containing Bioactive Bone Cement - Sun, Zhaoyao; Fu, Yuanfei; Chen, Demin (Asian Journal of Chemistry, 2013)
In this study, the influence of series of strontium substitutions on bioactive polymeric calcium phosphate cements has been evaluated in the present work. The cements were derived from a liquids that consisted of polcarboxylic acid (PCA), citric acid, potassium citrate and a calcium phosphate cement (CPC) powder that consisted of strontium-containing tricalcium phosphate (TCP ) and hydroxyapatite (HA) which is proved by the XRD and FTIR. A series of strontium-containing a-TCP/HA biphasic cement is prepared successfully. But the cement powder group of 20 atom % strontium amount was composition of b-TCP/HA biphase and did not set with the liquids.